Unveiling the diversity and mechanisms of plant growth-promoting bacteria in orchids: a comprehensive review - Ramzan, Faiza; Vassiliou, Loukia; Tsaltas, Dimitrios (Frontiers in Microbiology, 2026)
Orchids, one of the most diverse and ecologically important plant families, form complex associations with endophytic microorganisms that are vital for their survival, growth, and adaptation. These endophytes, including both fungi and bacteria, inhabit orchid tissues without causing harm and contribute to key physiological processes such as nutrient acquisition, stress tolerance, and disease resistance. This review explores the diversity and ecological roles of orchid-associated endophytes, emphasizing their significance in promoting germination, biomass production, and resilience to environmental stressors. Plant Growth-Promoting Bacteria (PGPB) such as Pseudomonas, Bacillus, and Burkholderia enhance nutrient uptake and plant defense, offering eco-friendly alternatives to chemical fertilizers and pesticides. Beyond ecological functions, endophytes show potential in biotechnology for sustainable agriculture, conservation, and novel bioactive compound discovery. Despite advances in molecular tools like metagenomics and next-generation sequencing, challenges persist in fully understanding and utilizing these microbes. This review highlights the need for multidisciplinary collaboration to optimize microbial inoculants, elucidate symbiotic mechanisms, and develop practical applications for conservation and sustainable horticulture. By integrating fundamental research with applied strategies, this work aims to unlock the full potential of orchid-associated endophytes in ecological and commercial domains.